Effect of Light Intensities and Nitrogen Fertilizer Dosages on Growth, Phenolics, and Flavonoid Production of Adenostemma lavenia - Shafira, Anisya Elsa; Aziz, Sandra Arifin; Farid, Muhammad; Ridwan, Taopik; Batubara, Irmanida (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Adenostemma lavenia (Asteraceae) is a medicinal plant considered a weed, consisted a lot of secondary metabolites, including phenolic and flavonoid. This species has been widely distributed in various countries but has yet to be widely cultivated. Thus, this study aimed to determine the highest plant growth, phenolic, and flavonoid production from A. lavenia cultivated under different shade of nitrogen fertilizers. The experiment used a nested design consisting of 2 factors. The first factor was shade with different intensities (0, 25, 50, and 75%) and the second was nitrogen fertilizer with different doses (0, 45, and 90 kg/ha). The highest plant was achieved at 50% shade level, while the highest leaf number and branch were 25% and 0%, respectively. Leaf thickness and stomata number increased in no-shade conditions. The production of phenolics and flavonoids was high under shaded conditions, supported by significantly high phenolics and flavonoid total under shade conditions, i.e., 35.94 mol gallic acid equivalent/plant and 21.76 mol quercetin equivalent/plant, respectively. A 90 kg/ha nitrogen fertilizer dose produced the best plant growth, phenolic, and flavonoid production. Keywords: Asteraceae, Heatmap, Nested design, Shade.